Providing An E-Business Framework For Malaysian Golf Industry In Global Market Perspective - Edrak, Bahrulmazi (2005)
The function of e-business concurrently can be worked as marketing tools to market any products and services in the global market, throughout the world. One of the parts of industry that benefits from this flourishing activity is golf industry. Therefore, this paper will be focused on finding a concept of e-business in the golf industry.